Does China’s centralized volume-based drug procurement policy facilitate the transition from imitation to innovation for listed pharmaceutical companies? Empirical tests based on double difference model - Gu, Yang; Zhuang, Qian (Frontiers in Pharmacology, 2023)
The normalized implementation of the centralized volume-based procurement policy for pharmaceuticals is a concerted push for supply-side structural reform of the pharmaceutical industry in China. The impact of the centralized drug procurement policy on pharmaceutical companies' transition from imitation to innovation is investigated to test whether a positive effect occurs in the innovation landscape of the pharmaceutical market. The double difference method and a series of robustness tests were used based on data from a sample of listed pharmaceutical companies in Shanghai and Shenzhen A-shares between 2015 and 2021. The study found that the centralized drug procurement policy significantly contributed to the increased intensity of innovation input in the Chinese pharmaceutical industry. In terms of regional and firm nature heterogeneity, it was found that firms in the seven provinces belonging to the three economic regions had a better increase in innovation input intensity than other regions. Firms of state-owned nature had a better increase in innovation input intensity than private companies. The mechanism test found a partial mediating effect of nearly 10% for the cost of sales rate on the innovation input intensity of listed companies and a negative mediating effect on corporate operating profit. Further research found that the effect of centralized drug procurement policy on the improvement of innovation quality of listed pharmaceutical companies was evident. The innovation development of Chinese pharmaceutical companies no longer focused on the accumulation of innovation quantity.